Cyber Crime And Criminal Law In The Era Of Artificial Intelligence - Murshal Senjaya (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The legal framework has significant potential to address cybercrime with the help of Artificial Intelligence (AI), which increases the efficiency of detecting, investigating and prosecuting increasingly sophisticated cybercriminals. This technology can perform big data analysis, pattern recognition and identification of suspicious behavior, but the legal framework needs to be updated to cover new crimes such as AI-based fraud and automated cyberattacks. The challenges in law enforcement related to the misuse of AI are quite complex, especially due to the lack of specific regulations to regulate its use in the context of cybercrime. Existing regulations often do not cover new situations, thus reducing the effectiveness of law enforcement. To overcome these challenges, legislators need to update regulations and develop ethical guidelines, while international collaboration and capacity building of law enforcement through education and training are also essential to increase the effectiveness of handling cybercrime.